Mother's Parenting Patterns in Forming the Independence of Cerebral Palsy Children at the Foundation for the Development of Disabled Children Jakarta - Syahputri, Dwisani; Nuralfiah, Nuralfiah; Annisa, Nur (International Journal of Social Science, Education, Communication and Economics, 2024)
The limitations of cerebral palsy sufferers mean that the child cannot fulfill his own needs and must get help from other people. Meanwhile, parents have high hopes for their children's independence. The research was conducted to find out and get a specific, detailed and clear picture of how mothers' parenting patterns shape the independence of children with cerebral palsy? Qualitative research using qualitative methods, as well as using source trangulation techniques. that each subject is able to act as the five roles, however, among the five parenting styles, there are parenting patterns that are the most dominant and those that are not dominant for each subject.